Development of Student Worksheet Based on Problem to Improve Student’s Mathematics Communication Skills - fardila hayati; Arief Aulia Rahman; Cut Eva Nasryah (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: This study aims to describe: (1) the validity of student worksheets based on problem; (2) increasing the mathematical communication skills of high school students by using student worksheets based on problem; (3) student responses to the development of student worksheets based on problem. This research is research and development. This research was conducted using Dick and Carrey model. The population in this study were all students of class X Darul Aitami private high school. Sampling used simple random sampling and the classes used as samples for the trial were class X-1 and class X-2. From the results of trial 1 and trial 2 it can be obtained: (1) student worksheets are included in the valid category, reviewed from several aspects, namely: format, language, material, and content. (2) the improvement of students 'mathematical communication skills by using student worksheets based on problem increased by 6.9%, in the first trial results the students' average score was 73.4% and after conducting the second trial it increased by 80.3%. (3) student responses to the components of student worksheets and learning activities using student worksheets are positive. Furthermore, it is suggested that teachers can use student worksheets based on problem as an alternative to learning, with the guidance or questions provided that are affordable to students, so that students understand the problems they are given more easily.